A secondary analysis of anthropometric data from the 1999 National Food Consumption Survey, using different growth reference standards - Bosman, Lise (Stellenbosch : Stellenbosch University, 2008)
Thesis (MNutr (Human Nutrition))--Stellenbosch University, 2008.